Circuit Weight Training Or Walking Exercise In Elderly Patients With Medicated Diabetes and Hypertension - Rosilene Andrade Silva Rodrigues; Fabrício Azevedo Voltarelli; Conceição de Maria Moita Machado de Carvalho; Giulia Schauffert; Waléria Christiane Rezende Fett; Carlos Alexandre Fett (Brazilian Society of Geriatrics and Gerontology, 2024)
BACKGROUND: There are different types of exercises, but the circuit weight training is less prescribed for the elderly in order to corroborate the control of glycaemia and hypertension. OBJECTIVE: To compare the acute and chronic effects of circuit weight training or walking exercises on capillary glucose, physical fitness, and arterial blood pressure of the elderly women. METHODS: Twelve weeks of circuit weight (n = 14) or walking (n = 9) were performed 3 times a week at the intensity of 40 to 60% heart rate, 11 to 13 in the Borg Scale. The elderly patients with medicated hypertension and diabetes (users of ß-blockers, angiotensin-converting enzyme inhibitors and oral hypoglycemic) were selected. RESULTS: The capillary glucose decreased in both groups in acute and chronic effects of exercise (p ≤ 0.05). The systolic blood pressure increased in acute moment only in the circuit weight (+6 mmHg, p ≤ 0.05) without differences in the diastolic blood pressure. The right handgrip, the balance of right and left legs, the sitting and standing test were improved in walking (p ≤ 0.05), and flexibility in circuit weight (p ≤ 0.05). There was no statistically significant difference in the left handgrip, subscapularis, lumbar back, and abdominal circumference, three-meters walking under line. There was no difference in the comparison between groups. CONCLUSION: The two types of exercises improve metabolic rehabilitation. Only 12 weeks of the circuit weight training seems to be a short period to induce higher physical performance in elderly women.